Intention Of Micro And Small Industry Entrepreneurs Toward Using Food Delivery Applications (Case Study In South Jakarta) - Hadi Nur Hadi; Rekarti Endi (Studia Ekonomiczne i Regionalne)
This study aims to analyze the relationship between the variables of security, information quality, ease of use perceived usefulness, and perceived trust toward intention to use online food delivery applications. The study involved 218 micro and small industry entrepreneurs in the culinary field.